KASUS PENYAKIT REPRODUKSI PADA ANJING BETINA DI RUMAH SAKIT HEWAN PROFESOR SOEPARWI TAHUN 2013 - , RIDWAN FITRA W, Dr. drh. Asmarani Kusumawati, MP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Job Training in Veterinary Hospital Profesor Soeparwi carried 10 to 16 March 2014. Objectives of this thesis to know the number of cases of reproductive disease in female dogs during 2013 and know how to handle it so that sustainability and the dog population can be maintained. Breeders should be able to manage and have good management of reproductive management. Existing disease in dogs vary, one of the disease in dogs is a reproductive disease. Results of reproductive disease cases in female dogs obtained from bookkeeping documents in Veterinary Hospital for years 2013. Reproductive disease in Veterinary Hospital cases was obtained with 43 cases. Types of cases of disease in Veterinary Hospital Profesor Soeparwi pyometra which amounted to 22 percent of cases by 51%, distokia were 8 cases with a percentage of 20%, abortion amounts to 5 percent of cases by 12%, endometritis amounted to 4 percent of cases with 10% fetal mummification amounted to 2 percent of cases with 5% fetal maceration and retained placenta amounted to 1 percent of cases with 2%.